Factors on the formation of asthma in children - Andrushchenko, Vira; Андрущенко, Віра Віталіївна (ХНМУ, 2022)
Scientists around the world are determining the extent to which genetic, hereditary and social factors influence asthma. The purpose of the study: to identify anamnestic risk factors for the development of asthma in children.
Фактори, що впливають на формування астми у дітей
Keywords: children; asthma; anamnestic risk factors